Multi-Site Study of Principal Leadership Management in Building Superior Junior High Schools - Ahmad Thohirin; Maria Veronika Roesminingsih; Warih Handayaningrum (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research examines the principal's strategy for building superior schools and how superior school service systems are built. Method: This research uses a descriptive qualitative approach, with a case study type and a multisite study design, where data collection uses in-depth interviews, observation, and documentation studies. The analysis uses data display, reduction, drawing conclusions, and verification. The subjects of this research were student guardians, administrators, school principals, and teachers. It was conducted at two Islamic boarding school-based private junior high schools in Lamongan Regency. Results: The principal's strategic management begins with a) School Self-Evaluation, strategic planning, strategy implementation, and strategy monitoring and evaluation; b) Formulating the Vision, Mission, and Goals of educational institutions involving all elements; c) Developing the quality of education begins with organizing teacher human resources starting from recruitment strategy, career development, improving welfare, further education as well as providing rewards and punishments, d) Creative and innovative learning management by the concept of an independent curriculum which is also modified with Islamic boarding schools curricula such as reciting the yellow book, tahfidz Qur'an program, and Dauroh, e) management of infrastructure facilities Novelty: The school principal's leadership strategy management will be effective if it is adjusted to the targets. This research is a community with a Santri background, so effective management of superior schools must also be based on Islamic boarding schools.